Redefining the phenotype of ALSP and AARS2 mutation–related leukodystrophy. (April 2017) - Lakshmanan, Rahul; Adams, Matthew E.; Lynch, David S.; Kinsella, Justin A.; Phadke, Rahul; Schott, Jonathan M.; Murphy, Elaine; Rohrer, Jonathan D.; Chataway, Jeremy; Houlden, Henry; Fox, Nick C.; Davagnanam, Indran
Abstract : Objective: To provide an overview of the phenotype of 2 clinically, radiologically, and pathologically similar leukodystrophies, adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) and alanyl-transfer RNA synthetase 2 mutation–related leukodystrophy ( AARS2 -L), and highlight key differentiating features. Methods: ALSP and AARS2 -L cases were identified from the adult-onset leukodystrophy database at our institution. In addition, cases with imaging findings were identified from a literature review. The phenotypic features were determined by combining published cases with those from our database. Results: A combined total of 74 cases of ALSP and 10 cases of AARS2 -L with neuroimaging data were identified. The mean age at onset was 42 years in ALSP and 26 years in AARS2 -L. Cognitive and motor symptoms were the most common symptoms overall in both. Ovarian failure was exclusive to AARS2 -L, present in all known female cases. Both ALSP and AARS2 -L showed a confluent, asymmetric, predominantly frontoparietal, periventricular pattern of white matter disease with subcortical U-fiber sparing; pyramidal tract and corpus callosum involvement; and diffusion changes in the white matter which we have termed "deep white matter diffusion dots." Central atrophy and corpus callosal thinning were prominent in ALSP and disproportionately mild in AARS2 -L when present. ALSP also occasionally showed ventricular abnormalities and calcifications in the frontal periventricular white matter, features not seen in AARS2 -L. AARS2 -L demonstrates white matter rarefaction which suppresses on fluid-attenuated inversion recovery MRI sequences, a feature not seen in ALSP. Conclusions: ALSP and AARS2 -L share similar clinical, imaging, and pathologic characteristics with key differentiating features that we have highlighted.